Cheap vs healthy: Analyzing McDonald’s menu using linear programming - Nur Fadhilah Ibrahim; Thurga Dewi Arunasalan; Nurul Akmal Mohamed (Bulletin of Electrical Engineering and Informatics, 2020)
The factors that influence food choices nowadays are time, cost and deliciousness. An obvious example is fast food. Although consumers are aware that fast food is not a healthy choice, many still chooses fast food because it is convenient. Therefore in this paper, by using linear programming, we analyzed McDonald’s Malaysia menu in order to find the cheapest menu and the ‘healthiest’ menu. We developed a linear programming model for McDonald’s Malaysia menu which adheres to Malaysia Recommended Nutrient Intake 2017 (RNI 2017). Then we solved the model and proposed the cheapest menu and also the ‘healthiest’ menu that meets the nutrient requirement based on RNI 2017. The result showed that price for the cheapest palatable menu is RM21.69 a day. For set menu, we found that no menu meets this requirement, suggesting that McDonald’s set menu should not be taken three times a day. The price for the ‘healthiest’ McDonald’s menu with the least total of fat, sugar and salt that meets the nutrient requirement is RM42.99 a day.